Creative research the theory and practice of reserach for the creative industries - Collins, Hilary (Lausanne : AVA Academia ; La Vergne, Tennessee : Distributed in the USA & Canada by Ingram Publisher Services, 2010)
Research For The Creative Industries' explores the practices & skills required for effective research in the creative industries. The book assesses how research methodologies must be adapted to suit the creative industries, & offers a guide to the process of undertaking a research project in this context.
Keywords: Industrial design -- Research -- Methodology; Industrial design -- Management; Design -- Research